Nitrogen removal and recovery from lagoon-pretreated swine wastewater by constructed wetlands under sustainable plant harvesting management. (June 2018) - Luo, Pei; Liu, Feng; Zhang, Shunan; Li, Hongfang; Yao, Ran; Jiang, Qianwen; Xiao, Runlin; Wu, Jinshui
Graphical abstract: Highlights: The contribution of plant harvests to N removal was dependent on the inlet loading rates. The recovered N mass via plant harvest was high at 21.8–282 mg N L −1 . The N removal via microbial process increased with increasing inlet loading rates. M. aquaticum can be used for nutrients recovery and wastewater treatment in CWs. Abstract: A series of three-stage pilot-scale surface flow constructed wetlands (CWs) planted with Myriophyllum aquaticum were fed with three strengths of lagoon-pretreated swine wastewater to study nitrogen (N) removal and recovery under sustainable plant harvesting management. The CWs had mean removal efficiency of 87.7–97.9% for NH4 + -N and 85.4–96.1% for total N (TN). The recovered TN mass via multiple harvests of M. aquaticum was greatest (120–222 g N m −2 yr −1 ) when TN concentrations were 21.8–282 mg L −1 . The harvested TN mass accounted for 0.85–100% of the total removal in the different CW units. Based on mass balance estimation, plant uptake, sediment storage, and microbial removal accounted for 13.0–55.0%, 4.9–8.0%, and 33.0–67.5% of TN loading mass, respectively. The results of this study confirm that M. aquaticum is appropriate for the removal and recovery of nutrients in CW systems designed for treating swine wastewater in conjunction with sustainable plant harvesting strategies.